Enzymatic synthesis of an orlistat intermediate using a mutant short-chain dehydrogenase from Novosphingobium aromaticivorans. (August 2020) - Tang, Yunping; Zhou, Yafeng; Zhao, Qiaojun; Zhao, Qiaoling; Wang, Zhao
Graphical abstract: Highlights: The orlistat intermediate was first produced by a mutant short-chain dehydrogenase. The reaction was catalyzed by this enzyme with an enantiomeric excess of 99 %. Using 50 g/L crude enzyme, 50 g/L substrate was completely reduced in 24 h. Abstract: Methyl (R)-3-hydroxytetradeconoate ((R)-MHOT) is a crucial chiral intermediate for the chemical synthesis of the anti-obesity drug, orlistat. Here, (R)-MHOT was prepared from methyl 3-oxotetradecanoate (MOT) using a mutant of the short-chain dehydrogenase/reductase (SDR) from Novosphingobium aromaticivorans (NaSDR). Mutant NaSDR-G145A/I199L had a 3.23 times greater k cat value than that of wild type toward MOT. The conditions for the expression of recombinant NaSDR-G145A/I199L were further investigated and obtained cells were used for gram-scale preparation of (R)-MHOT with 50 g/L of MOT. The target product was extracted and confirmed by gas chromatography; the enantiomeric excess value of (R)-MHOT was 99.0 %. Molecular docking analysis was used to reveal the molecular basis of the enhanced catalytic activity of NaSDR-G145A/I199L; NaSDR-G145A/I199L presented a more effective docking posture than NaSDR. This is the first reported use of SDR for preparing (R)-MHOT via the reduction of MOT. Our study provides a foundation for greener preparation of (R)-MHOT.